Densitometry, radiography, and histological assessment of collagen as methods to evaluate femoral bones in an experimental model of osteoporosis - Hernandes, L.; Ramos, A. L.; Micheletti, K. R.; Santi, A. P.; Cuoghi, O. A. [UNESP]; Salazar, M. (Springer London Ltd, 2012)
All methods to detect experimental loss of bone present technique limitations. The sensitivities of image and histological analyses to detect the effects of teriparatide in rats with bone loss after ovariectomy were evaluated. All methods were qualitatively valid.The standardization of methods to assess bone loss after ovariectomy is crucial to establish the degree of experimental osteoporosis. In general, methods per image or histological techniques are used. To validate these two ways to determine the degree of bone loss in ovariectomized rats, we evaluated the sensitivities of bone densitometry, conventional radiography, and histological analysis of the area occupied by collagen, detecting the effects of teriparatide treatment in the femur of ovariectomized rats with bone loss.Wistar rats were divided into three groups: a control group, in which the animals were only subjected to laparotomy; an ovariectomized group, in which bilateral removal of the ovaries was performed; and an ovariectomized + teriparatide group, in which bilateral removal of the ovaries was performed, and the animals were treated with 3 mu g/100 g/day of teriparatide. Three months following the ovariectomy, bone densitometry, radiographic densitometry, and histological analysis of the area occupied by collagen fibers were carried out in the femur diaphysis.The bone densitometry revealed 11.2% reduction in femur density; in the conventional radiography, the loss of bone mass was 14.5%, and with the histological analysis, a 40.9% reduction in the area occupied by collagen was detected in the femur diaphysis.In conclusion, histological analysis could not be quantitatively compared with the methods of bone densitometry and conventional radiography; however, all of these methods were qualitatively valid for assessing the loss of bone stemming from ovariectomy and the therapeutic effect of teriparatide in the prevention of osteoporosis.
Keywords: Densitometry; Histology; Osteoporosis; Ovariectomy; Radiographic densitometry